Protection Effects of Vernonia Amygdalina Methanolic Extracts Against Hepatocellular Damage Induced by Petroleum Contaminated Diets in Male Rats - ACHUBA, FIDELIS IFEAKACHUKU; Ichipi-Ifukor, Patrick Chukwuyenum (Iraqi Journal of Science, 2020)
Recently, bitter leaf (Vernonia amygdalina) was found to prevent petroleum – induced toxicities on the kidney whereas it potentiates the toxic effect of petroleum adulterated diet on the testes of animal model. This differential action has elicited further inquest into the role of bitter leaf extract in other organs in the midst of petroleum affronts. The hepatoprotective ability of Vernonia amygdalina methanol extract (VAME) is the objective of this investigation. Administration of VAME significantly (P <0.05) reduced serum liver function indices relative to the control. In addition, the activities of liver oxidative enzymes, energy metabolizing enzymes and oxidative stress indices altered by crude oil adulterated diet were significantly (P < 0.05) reversed near control values. Similarly, VAME injection restored the histopathological indices caused by crude oil adulterated diet. It is obvious that all the liver damage indices induced by crude oil contaminated feed were prevented by the intake of VAME, indicating the hepatoprotective ability of bitter leaf